A COMPARATIVE STUDY ON THE COGNITIVE AND METACOGNITIVE STRATEGIES OF 6th GRADE PRIVATE AND STATE SCHOOL STUDENTS USE WHILE READING SCIENCE TEXTS - Diken, Emine Hatun (International Online Journal of Education and Teaching, 2020)
The aim of this qualitative case study was to determine the cognitive and metacognitive strategies used by the Secondary School 6th grade students while reading science texts in a Biology unit titled "Support and Motor System", and to compare these strategies in accordance with the type of their school (private or state school), their grade point averages and their perceptions concerning the difficulty level of the chapter. The number of the participant students was 6; 3 from a private school and 3 from a state school. After the students read the texts in the unit, semi structured interviews were administered in order to determine their strategy types, to compare and contrast these strategies in accordance with the type of their schools, their grade point averages and their perceptions concerning the difficulty level of the chapter. The results of the study revealed that the private school students had “High” and “Very high” grade point averages and assessed the chapter as "Easy” and “Very Easy”, used a higher number and a wider variety of cognitive and metacognitive strategies whereas the state school students had “Low” and "Very Low" grade point averages and assessed the chapter as "Difficult" and "Very Difficult".